A novel interaction between hydrogen peroxide metabolism and LDL-uptake controls immunergulatory properties in human dendritic cells - Potential implications for tumor immune escape - Menzner, Ann-Katrin; Rottmar, Tanja; Bosch, Jacobus J.; Mougiakakos, Dimitrios; Mackensen, Andreas; Resheq, Yazid; Völkl, Simon (CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2021-03-05

A Protocol for In Vitro High-Throughput Chemical Susceptibility Screening in Differentiating NT2 Stem Cells - Menzner, Ann-Katrin; Gilbert, Daniel (Methods in Molecular Biology, 2017)
The incidence of neurological diseases including learning and developmental disorders has increased in recent years. Concurrently, the number and volume of worldwide registered and traded chemicals have also increased. There is a broad consensus that the developing brain is particularly sensitive to damage by chemicals and that evaluation of chemicals for developmental toxicity or neurotoxicity is critical to human health. Human pluripotent embryonal carcinoma (NTERA-2 or NT2) cells are increasingly considered as a suitable model for in vitro developmental toxicity and neurotoxicity (DT/DNT) studies as they undergo neuronal differentiation upon stimulation with retinoic acid (RA) and allow toxicity assessment at different stages of maturation. Here we describe a protocol for cell fitness screening in differentiating NT2 cells based on the analysis of intracellular ATP levels allowing for the identification of chemicals which are potentially harmful to the developing brain. The described method is suitable to be adapted to low-, medium-, and high-throughput screening and allows multiplexing with other cell fitness indicators. While the presented protocol focuses on cell fitness screening in human pluripotent stem cells it may also be applied to other in vitro models.
Keywords: Cell fitness; Cell viability; Cell-based assays; CellTiter-Glo Luminescent Cell Viability Assay; Chemical susceptibility; DNT; Developmental toxicity and neurotoxicity; Differentiation; Drug discovery; Drug screening; High-throughput screening; In vitro toxicity screening; Neurotoxicity; Target validation

Corrigendum to "Towards in vitro DT/DNT testing: Assaying chemical susceptibility in early differentiating NT2 cells" [Toxicology 338 (2015) 69-76]. - Menzner, Ann-Katrin; Abolpour Mofrad, Sepideh; Friedrich, Oliver; Gilbert, Daniel (Toxicology, 2017)

Hydrogen-peroxide synthesis and LDL-uptake controls immunosuppressive properties in monocyte-derived dendritic cells - Menzner, Ann-Katrin; Rottmar, Tanja; Bosch, Jacobus J.; Mougiakakos, Dimitrios; Mackensen, Andreas; Resheq, Yazid; Völkl, Simon (Cancers, 2021)
Given the encouraging success of immunotherapy in cancer, the role of metabolism in tumor immune-evasion is an emerging research field with a unique potential to overcome current limitations in immunotherapy. Herein, hepatic stromal cells, which may act as immunological bystanders in cancer, are capable of inducing immunosuppressive phenotypes in monocytic cells by controlling hydrogen peroxide (H2O2-) metabolism. As monocytic cells play an important role in tumor-immunology, we sought to identify the underlying mechanisms. Herein, we unraveled a complex interaction between cholesterol/LDL- and H2O2-metabolism: Extracellular depletion of H2O2 leads to enhanced H2O2-production with a consecutive increase in LDL-uptake throughout differentiation of monocytes to monocyte-derived dendritic cells and, as a result, to the induction of distinct immunosuppressive properties. These findings shed new light on the role of LDL-metabolism in tumor-immunology and might help to further improve immunotherapeutic approaches against cancer. Background and Aims: Induction of myeloid-derived suppressor cells (MDSC) is a critical step in immune cell evasion by different cancer types, including liver cancer. In the liver, hepatic stromal cells orchestrate induction of MDSCs, employing a mechanism dependent on hydrogen peroxide (H2O2) depletion. However, the effects on monocyte-derived dendritic cells (moDCs) are unknown. Methods: Monocytes from healthy donors were differentiated to moDCs in the presence of extracellular enzymatic H2O2-depletion (hereinafter CAT-DCs), and studied phenotypically and functionally. To elucidate the underlying molecular mechanisms, we analyzed H2O2- and LDL-metabolism as they are interconnected in monocyte-driven phagocytosis. Results: CAT-DCs were of an immature DC phenotype, particularly characterized by impaired expression of the costimulatory molecules CD80/86. Moreover, CAT-DCs were able to suppress T-cells using indoleamine 2,3-dioxygenase (IDO), and induced IL10/IL17-secreting T-cells-a subtype reported to exert immunosuppression in acute myeloid leukemia. CAT-DCs also displayed significantly increased NADPH-oxidase-driven H2O2-production, enhancing low-density lipoprotein (LDL)-uptake. Blocking LDL-uptake restored maturation, and attenuated the immunosuppressive properties of CAT-DCs. Discussion: Here, we report a novel axis between H2O2- and LDL-metabolism controlling tolerogenic properties in moDCs. Given that moDCs are pivotal in tumor-rejection, and lipid-accumulation is associated with tumor-immune-escape, LDL-metabolism appears to play an important role in tumor-immunology.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Catalase; Hydrogen peroxide; IDO; LDL-uptake; Reactive oxygen species; Tolerogenic dendritic cells; Tumor immune escape

Impaired Transmigration of Myeloid-Derived Suppressor Cells across Human Sinusoidal Endothelium Is Associated with Decreased Expression of CD13 - Resheq, Yazid J.; Menzner, Ann-Katrin; Bosch, Jacobus J.; Tickle, Joseph; Li, Ka-Kit; Wilhelm, Annika; Hepburn, Elizabeth; Murihead, Gillian; Ward, Stephen T.; Curbishley, Stuart M.; Zimmermann, Henning W.; Bruns, Tony; et al. (Journal of Immunology, 2017)
Human monocytic myeloid-derived suppressor cells (MO-MDSCs) within the hepatic compartment suppress inflammation and impair immune surveillance in liver cancer. It is currently not known whether recruitment of MO-MDSCs from blood via hepatic sinusoidal endothelium (HSEC) contributes to their enrichment within the hepatic compartment. We compared the transmigratory potential of MO-MDSCs and monocytes after adhesion to hepatic endothelial monolayers in flow-based assays that mimic in vivo shear stress in the sinusoids. Despite comparable binding to HSEC monolayers, proportionally fewer MO-MDSCs underwent transendothelial migration, indicating that the final steps of extravasation, where actin polymerization plays an important role, are impaired in MO-MDSCs. In this article, we found reduced levels of CD13 on MO-MDSCs, which has recently been reported to control cell motility in monocytes, alongside reduced VLA-4 expression, an integrin predominantly involved in adherence to the apical side of the endothelium. CD13 and VLA-4 blocking and activating Abs were used in flow-based adhesion assays, live-cell imaging of motility, and actin polymerization studies to confirm a role for CD13 in impaired MO-MDSC transmigration. These findings indicate that CD13 significantly contributes to tissue infiltration by MO-MDSCs and monocytes, thereby contributing to the pathogenesis of hepatic inflammation.
EVALuna2:25713

Towards in vitro DT/DNT testing: Assaying chemical susceptibility in early differentiating NT2 cells. - Menzner, Ann-Katrin; Abolpour Mofrad, Sepideh; Friedrich, Oliver; Gilbert, Daniel (Toxicology, 2015)
Human pluripotent embryonal carcinoma (NT2) cells are increasingly considered as a suitable model for in vitro toxicity testing, e.g. developmental toxicity and neurotoxicity (DT/DNT) studies, as they undergo neuronal differentiation upon stimulation with retinoic acid (RA) and permit toxicity testing at different stages of maturation. NT2 cells have recently been reported to show specific changes in dielectric resistance profiles during differentiation which can be observed as early as 24 h upon RA-stimulation. These observations suggest altered susceptibility to chemicals at an early stage of differentiation. However, chemical susceptibility of early differentiating NT cells has not yet been studied. To address this question, we have established a cell fitness screening assay based on the analysis of intracellular ATP levels and we applied the assay in a large-scale drug screening experiment in NT2 stem cells and early differentiating NT2 cells. Subsequent analysis of ranked fitness phenotypes revealed 19 chemicals with differential toxicity profile in early differentiating NT2 cells. To evaluate whether any of the identified drugs have previously been associated with DT/DNT, we conducted a literature search on the identified molecules and quantified the fraction of chemicals assigned to the FDA (Food and Drug Administration) pregnancy risk categories (PRC) N, A, B, C, D, and X in the hit list and the small molecule library. While the fractions of the categories N and B were decreased (0.81 and 0.35-fold), the classes C, D and X were increased (1.35, 1.47 and 3.27-fold) in the hit list compared to the chemical library. From these data as well as from the literature review, identifying large fractions of chemicals being directly (42%) and indirectly associated with DT/DNT (32%), we conclude that our method may be beneficial to systematic in vitro-based primary screening for developmental toxicants and neurotoxicants and we propose cell fitness screening in early differentiating NT2 cells as a strategy for evaluating chemical susceptibility at different stages of differentiation to reduce animal testing in the context of the 3Rs.
Keywords: Developmental toxicity and neurotoxicity testing; Chemical susceptibility; Cell viability screening; Human pluripotent embryonal carcinoma cells Differentiation